Green infrastructure planning based on ecosystem services multicriteria evaluation: the case of the metropolitan wine landscapes of Bordeaux - Giovanna Calia; Vittorio Serra; Antonio Ledda; Andrea De Montis (Journal of Agricultural Engineering, 2023)
Excessive anthropogenic activities affect landscape patterns and trigger a decrease of natural capital and the level of quality of life. Green infrastructures (GIs) are commonly accepted by scholars as solutions for restoring degraded areas and providing a variety of ecosystem services (ESs). The other way around, the capacity to deliver ESs can be assumed as a relevant starting point for GIs analysis and planning. The assessment of ESs needs extensive investigation and applications, to provide planners, policy makers, and institutional stakeholders with an adequate evaluation tool. The multi-facet nature of ESs assessment implies the use of complex tools able to consider many concerns. In this regard, multicriteria analysis (MCA) is a very popular tool due to its capacity to intertwine a variety of issues in a rigorous way and to support participatory and transparent decision making in the public domain. In this study, we aim at contributing to the integration of GI design into spatial planning starting from the assessment of the net benefit delivered to local society by a GI in the metropolitan area of Bordeaux (France). We assessed the net benefit by confronting the ESs deliverable by the GI and the cost sustained for its construction and maintenance. We applied an MCA-based method to the selection of the most efficient alternative out of three GI paths. We demonstrate that our method is useful for the assessment of cultural and regulating ESs, comparing the GI design alternatives, and considering the preference model of the stakeholders within GI planning and design.